Toward wellness : prevention, coping, and stress - Gates, Gordon S.; Wolverton, Mimi (Research on stress and coping in education series., 2002)
This series of Works on stress and coping is centered on understanding the sources, experiences, and consequences of stress and coping in the educational arena. In formal organizations to informal experiences, those engaged in educational endeavors shape and are shaped by events and interactions that invoke salient to subtle stress and coping responses. We invite authors to submit manuscripts that present studies focused on stress and/or coping in any of the contexts, positions, peoples, and activities encompassed under the umbrella of education. Research using either qualitative or quantitative methodologies will be acceptable. The series is expected to appeal to a broad readership of scholars in the fields of education, psychology, sociology, and business who are interested in understanding the nature of stress and coping in education.